2006
DOI: 10.1038/sj.bjp.0706825
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide B and W: neurotransmitters in an emerging G‐protein‐coupled receptor system

Abstract: Deorphanised G-protein-coupled receptors represent new and expanding targets for drug development. Neuropeptide B (NPB) and W (NPW) have recently been identified as the cognate endogenous ligands for the orphan receptor GPR7, now designated as NPBW 1 . NPB and NPW also bound to a second related orphan receptor, GPR8, now designated as NPBW 2 that is present in humans but not rats or mice. In humans, high levels of NPW mRNA have been visualised in the substantia nigra, whereas moderate expression levels have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…The dog has three chromosomes and the opossum has two chromosomes that correspond to chicken chromosome 3 indicating that the translocations in mammals occurred in two steps. It has been suggested that the NPBW receptors are closely related to both the opioid and the somatostatin receptors (44,45). The phylogenetic tree (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The dog has three chromosomes and the opossum has two chromosomes that correspond to chicken chromosome 3 indicating that the translocations in mammals occurred in two steps. It has been suggested that the NPBW receptors are closely related to both the opioid and the somatostatin receptors (44,45). The phylogenetic tree (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents where NPBWR2 is absent, its counterpart is described as being similar to neuropeptide B/W receptor 2 (formerly GPR8-like) (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…However, since no biochemical and pharmacological data are available at present, this hypothesis remains to be proved in future studies. Since an autoradiographic study has shown that high levels of 125 I-labeled NPB or NPW bindings are detected in the SCN (11,29), functional receptors may be expressed in the SCN. However, there are many evidences that they are functionally inactive.…”
Section: Anticipation Of Feeding In Restricted Feeding Schedule In Gpr7mentioning
confidence: 99%
“…Recently, its two endogenous ligands, neuropeptide B (NPB) and neuropeptide W (NPW), were identified (3,6,28,30). Although roles of this receptor on feeding, prolactin-release and pain were reported (29), the roles of GPR7 on biological rhythms have not been clarified. In the present study, we demonstrated the circadian change of GPR7 expression in the SCN, and further examined the circadian characteristics of mice deleted with GPR7 gene (10).…”
mentioning
confidence: 99%